Emancipating Student Autonomous Learning using Integrated Entrepreneurship Videos of Schoology Application - Sudarwati, Ninik; Nurdian, Nurdian; Prianto, Agus (Jurnal Sains Sosio Humaniora, 2020)
E-learning requires students to study the material that has been uploaded to Schoology app independently. It also included independent and open discussion among students under the guidance of the lecturer in charge. The purpose of this research is to describe student independence in entrepreneurial learning using integrated entrepreneurship video in Schoology LMS application. It is a qualitative research which describes student independence in terms of learning, answering questions, and peer reviewing. This research was conducted from March to September 2019, involving 26 students as the informants. The data collection method used was participatory; the researchers played a key role as lecturers. The results of the study show that students can download an open the application easily. They did the tasks on time, learned the material (in the form of PowerPoint slide) on new entrepreneurial product ideas, learned the videos, conveyed general ideas, answered psychomotor questions after learning the videos, and conduct peer reviewing independently. In general, students learned entrepreneurship through videos in Schoology LMS application independently.